On The Performance Of The Motorcycle Engine Using Filtered Recycle Lubricant Oil - Mohd Azam, Muhammad Azfar Razin (Universiti Sains Malaysia, 2018)
Once the service life of lubricating oil is over for a particular use, the deterioration is obviously there but at the same time major part of the oil remains in good condition and can be regenerated. There are many physical and chemical processes which have been employed valuable to recover the used oil. By incorporating suitable additives into the used lubricating oils, most of the properties of the oil can be modified to produce finished oil which may have same properties as that of the virgin oil. Moreover, the environmental legislation of countries does not allow their disposal in any type of soils, rivers, lakes, oceans or sewerage systems. In this study, the engine oil that has been used for several mileages undergo filtration process in order to remove wear debris from contamination that lead to damaging piston and others mechanical component inside engine. The viscosity of each grade lubricant oil will be compared after filtration process and analyse heat build up. The filtered lubricant oil will be used to study the effect on the engine performance, particularly the torque and power of the engine. The effect will be analyses whether it is safe to use or not. The engine was run using different types of filtered oil at Wide Open Throttle (WOT). The performance graph will be compared with base engine oil. Result showed that there were slight drop in performance which are the torque is in the range of around 0.73% - 2.46% whereas the power is in the range between 0.9% -3.2%. The filtered lubricant oil show high torque and brake power compared to used engine oil. This is because filtered lubricant oil has less carbon deposit which consequent affect the efficiency too. The filtered lubricant oil and baseline oil operates under temperature around 80 until 90 degree Celsius, whereas the used mineral oil operates under temperature around 90 until 110 degree Celsius.